Posted by **C.S.** on Monday, October 15, 2012 at 11:20am.

deriv.

y=x(sinx)(cosx)

- Calc -
**bobpursley**, Monday, October 15, 2012 at 11:22am
y=uvw

y'=vwu' + uvw'+uwv'

It is just algebra, and probably some trig identities.

- Calc -
**Steve**, Monday, October 15, 2012 at 11:25am
use the product rule.

hard way:

(1)[(sinx)(cosx)] + {x(cosx)](cosx) + [x(sinx)](-sinx)

= sinx cosx + xcos^2 x - xsin^2 x

= 1/2 sin 2x + xcos 2x

easier way:

y = 1/2 x sin 2x

y' = 1/2 (sin 2x) + 1/2 x (2cos 2x)

= 1/2 sin 2x + x cos 2x

## Answer this Question

## Related Questions

- Pre-Calc - Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= ...
- Trig........ - I need to prove that the following is true. Thanks (cosx / 1-sinx...
- ap calc bc - hi! ok, i know that deriv(cscx) = -cscxcotx and that deriv(cos) = -...
- Trigonometry Check - Simplify #3: [cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [...
- Trigonometry. - ( tanx/1-cotx )+ (cotx/1-tanx)= (1+secxcscx) Good one! ...
- Pre-calc - prove the identity: (cosx)(tanx + sinx cotx)=sinx+cos(squared)x i ...
- Math - Verify the identity . (cscX-cotX)^2=1-cosX/1+cosX _______ sorry i cant ...
- Math - Pre- Clac - Prove that each of these equations is an identity. A) (1 + ...
- trigonometry - can i use factoring to simplify this trig identity? the problem ...
- Mathematics - Trigonometric Identities - Prove: (tanx)(sinx) / (tanx) + (sinx...